Navigating the rivers of sustainability in the Amazon: the dilemma of accounting for carbon credits - Aleff dos Santos Santana; Juh Círico; Claudio de Souza Miranda; Alessandra de Fátima Souza de Souza; Rayane de Lima Silva Belo (Revista Ambiente Contábil)
Purpose: The education case in this paper aims to encourage discussions about accounting for carbon credits by presenting a fictional story about a female accountant who is head of an ecologically sustainable family business called Econorte. Lecturers and students from accounting courses will be able to discuss the bookkeeping issues for sustainable companies that use carbon credits.